Preparation of highly exfoliated epoxy/clay nanocomposites by clay grafted with liquid crystalline epoxy. Issue 3 (19th February 2017) - Chen, Fei; Cong, Yuehua; Zhang, Baoyan; Wang, Zeqing; Yao, Bing
ABSTRACT: Epoxy/clay nanocomposites with a high degree of exfoliation were achieved by intercalating liquid crystalline epoxy into clay intragallery as well as using a so-called 'solution compounding' process. In this process, clay modified was first treated with trichloromethane to form organoclay-trichloromethane suspension followed by liquid crystalline epoxy modification. The liquid crystalline epoxy grafted clay was then mixed extensively with epoxy to form epoxy/nanoclay composites. The mechanism of exfoliation was explored by monitoring the change of morphology of organoclay during each stage of processing with X-ray diffraction (XRD). The liquid crystalline epoxy grafted clay synthesised was characterised by fourier transform infrared spectroscopy (FT-IR) and polarising optical microscopy (POM). The clay platelets uniformly dispersed and highly exfoliated in the whole epoxy matrix were observed using transmission electron microscopy (TEM) and FT-IR imaging system. The epoxy nanocomposites were fabricated by incorporating different liquid crystalline epoxy grafted clay loading. The results revealed that the incorporation of liquid crystalline epoxy grafted clay resulted in a significant improvement in glass transition temperature (Tg) derived from dynamic mechanical analysis (DMA) and thermal stability measured by thermogravimetric analysis (TGA). GRAPHICAL ABSTRACT: